INDIGENOUS ECUADORIANS’ CHALLENGES AND ATTEMPTS TO COMBAT EXTRACTIVE INDUSTRIES: A HUMAN RIGHTS-BASED APPROACH - Zahidi, M. Syaprin (Jurnal Ilmiah Dinamika Sosial, 2022)
Ecuador is remarkably known as the first country that granted natural constitutional rights.  However, it still does not guarantee its nature preservation. This Latin American country is also highly dependent on oil. The dilemma of the continuity of the extractive industries emerged in the discussion. This influences indigenous peoples' unmet rights, especially when they are the ones who are directly affected by climate change as forest dwellers. To defend their territories, indigenous people in Ecuador do not stand still. Indigenous rights and sovereignty over their lands are becoming more widely recognized, which may prevent the Amazon from further damage. This research aims to investigate the actions and challenges that Indigenous Ecuadorians must face in combatting extractive industries. The authors use a descriptive qualitative approach and collect data from library research. This study uses a human rights-based approach to analyze the content of this paper.  As a result, this research found that Ecuador’s government which plays the duty-bearer is failing and lacking the obligations to protect indigenous rights. On the other side, the indigenous people in Ecuador are thriving to defend their rights by reflecting on the human rights-based approach's five principles: participation, accountability, non-discrimination and equality, empowerment, and legality. Indigenous peoples and environmental groups are not enabling misery or hunger by supporting the environmentally practical measure.